A Philosophical Analysis of the Experience of Will and Its Weaknesses - Wiśniewski, Ryszard (Filozofia Chrześcijańska, 2013)
The starting point of the analysis of the will and its weaknesses is the experience of the will, which the author brings first to experiencing morning awakening and undertaking daily activities. He does this in order to capture the different forms of manifestation of the will and the ways of its operation, especially weakening. Such forms are: (1) automated, habitual, enslaved will; (2) weak, sluggish, lazy will, (3) autonomous, bossy will, implementing the provisions in a certain distance from their adoption; (4) strong will, persistently focused on overcoming weaknesses, putting out a challenge to them; (5) willfulness, will undergoing desires unacceptable by reason, the extreme lack of self-control. The author notices that the first and fifth form of the participation of the will in the management of human behavior show certain resemblance because in fact they are weakening as we are giving in to habits and addictions. The second form of the will is discussed in the context of the theory of sloth. The third one is treated as the power responding to tasks and duties assigned by the mind, but also motivated by the awareness of evil hurting the subject as a result of not- -undergoing orders of reason. The strong will is associated with the need to protect values as well as with the need to strive after perfection and to overcome barriers. The author is comparing the above interpretations of experiencing the will with the classical and contemporary analysis of it, with the discovery of its relationship to the intellect and with identifying the causes of the inability of implementing its precepts. It results from these analyses that the weakness of the will is an indication of the axiological disintegration of man and that overcoming the axiological chaos is the way to improve the will.